A prospective, phase II study on the safety and efficacy of negative pressure closure for the stabilization of split‐thickness skin graft in large or muscle‐exposing defects: The NPSG study. Issue 9 (24th May 2021) - Nakamura, Yoshiyuki; Ishitsuka, Yosuke; Sasaki, Katsuhito; Ishizuki, Shoichiro; Tanaka, Ryota; Okiyama, Naoko; Furuta, Junichi; Fujimoto, Manabu; Yamada, Takeshi; Fujisawa, Yasuhiro
Abstract: Several studies have demonstrated the usefulness of negative pressure closure (NPC) for the stabilization of skin grafts because it provides a uniform pressure to the graft. The results of our previous retrospective study also suggested the superiority of NPC over tie‐over methods for the stabilization of split‐thickness skin graft (STSG) in large or muscle‐exposing defects. However, the usefulness of NPC for graft stabilization is yet to be fully established. This prospective, phase II clinical study was conducted to investigate the safety and efficacy of NPC for the stabilization of STSG in large or muscle‐exposing defects. Patients who would require STSG for reconstruction of defects in the trunk and extremities other than hands and feet measuring >10 cm in the longest diameter or with muscle exposure were enrolled. NPC was applied for skin graft stabilization. Seven patients who had received wide excision of malignant tumors and resulted in muscle‐exposed skin defects were included. All patients underwent meshed STSG. The mean size of the defect was 94.5 cm 2 (range 63.6–164.9). The mean time from the skin graft harvesting to the NPC stabilization was 15.6 min (range 10.7–19.5). The mean survival rate of the skin graft at postoperative day 7 and 10 was 98.7% (range 97–100) and 96.5% (range 89.4–98.4), respectively. No adverse events associated with the procedure were observed. This prospective study provided further evidence of the safety and efficacy of NPC for STSG stabilization in patients with large or muscle‐exposing skin defects.